Secondary School Student’s Academic Performance Self Esteem and School Environment: an Empirical Assessment from Nigeria - Olubunmi, Gegelesho; Kolawole, Ayodele (PT. Riset Press International, 2023)
Exams have long served as the primary tool for determining a student's aptitude and as a way to choose students for academic advancement and employment. This study evaluated how much the school atmosphere and students' self-esteem affected their academic performance in a few senior secondary schools in Obafemi-Owode LGA, Ogun State, Nigeria. A survey research design was adopted. Three hundred and ninety-six (396) respondents participated in the study. Descriptive statistics of frequency distribution mean and standard deviation was used to analyze the data and provide answers to the research questions. The study found that self-esteem levels, academic achievement levels, and respondents' perceptions of the school environment were all below average for secondary school pupils. In order to increase students' academic engagement and performance, the study found that secondary school students' self-esteem and a supportive school climate are important elements that should be taken into consideration together. The study did, however, suggest that parents and teachers must work together to foster a welcoming and encouraging learning atmosphere where students feel fully supported, motivated, and appreciated.